Differences in Depression Based on Stigma among Caregiver Female of People with Schizophrenia - Franky Hadinata Sitepu; Harun T. Parinduri; Vita Camellia (Budapest International Research and Critics University, 2020)
Schizophrenia is a serious mental disorder characterized by fundamental disturbances in thinking, perception and emotions. In addition to the burden felt directly by the sufferer, the family or relatives of the person with schizophrenia also experience the same burden. This family cared for them in their home, participated in treatment and rehabilitation. The World Health Organization (WHO) reports that stigma is one of the biggest obstacles in dealing with mental disorders. Overcoming stigma is very important in reducing depression rates in families of people with schizophrenia. This study was a cross sectional study using a categorical comparative analytic design, which was conducted at RSJ Prof. dr. M. Ildrem Medan, North Sumatra from June to December 2019. The research subjects were 86 female caregivers of people with schizophrenia. The measuring instrument used to assess stigma is the Stigma Items from the Schedule for Clinical Assessment in Neuro Psychiatry (SI from SCAN) / Family Interview Scale, and depression is assessed using the Beck Depression Inventory II (BDI-II). From all research subjects, it was found that 72 subjects (83.7%) experienced severe stigma to date and 14 subjects (16.3%) experienced mild stigma in caring for family members who suffer from schizophrenia. The results of the analysis using the chi-square test obtained p value = 0.001 (p <0.05). There was a very significant difference in depression based on the stigma of female caregivers of people with schizophrenia.